Bioplastics are revolutionizing the packaging industry - Ehman, Nanci Vanesa (2021)
The production of bioplastics is a growing trend. The utilization of renewable sources, in some cases currently wasted, to replace petroleum derivatives, is providing opportunities to achieve more environmentally friendly product life cycles. The possibility of producing biodegradable products under normal environmental conditions is another goal of recent studies. This editorial summarizes current aspects in the production of bioplastics. We highlight new studies that make it possible to obtain biodegradable composites using a natural, renewable, high availability, and low-cost material, such as cellulose.